Implications of gender-focused research in Senegal for farmer's adaption to climate change - Kristjanson, Patricia; Bernier, Quinn; Bryan, Elizabeth; Ringler, Claudia; Meinzen-Dick, Ruth S.; Ndour, Yacine Badiane; Kovarik, Chiara; Haglund, Eric; Quiros, Carlos; Herrero, Mario; Rufino, Mariana; Silvestri, Silvia; et al. (International Food Policy Research Institute, 2015)
Crop and climate models predict how climate change will impact yields of various crops in different regions. However, it is difficult to predict the impact of climate change on individuals’ lives. Different groups and types of people experience the impacts of climate change differently depending on their position in society, which is determined by gender, race, class, ethnicity, religion, age, and other factors. Local cultural and gender norms regarding who does what and who controls the benefits from different activities also matters. It stands to reason, then, that appropriate climate change adaptation strategies, including adoption of climate-smart agricultural practices and use of climate information, will be distinct for different groups of people, and for women compared to men.